2009
DOI: 10.1167/iovs.08-2272
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Sub-retinal Pigment Epithelium Morphologies of Exudative Macular Diseases by High-Penetration Optical Coherence Tomography

Abstract: LP-OCT provided significant improvement in the image contrast of exudative macular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 30 publications
4
52
0
Order By: Relevance
“…12 Yasuno et al compared images obtained using long wavelength OCT to the standard 830nm FD-OCT in visualising the morphology of structures beneath the RPE, such as choroidal neovascular membranes. They found a general improvement in the image contrast of sub-RPE structures in most eyes and, in 3 eyes, were able to see hyper-reflective structures beneath the choroidal neovascular membranes, not accessible using the 830nm OCT.…”
Section: Discussionmentioning
confidence: 99%
“…12 Yasuno et al compared images obtained using long wavelength OCT to the standard 830nm FD-OCT in visualising the morphology of structures beneath the RPE, such as choroidal neovascular membranes. They found a general improvement in the image contrast of sub-RPE structures in most eyes and, in 3 eyes, were able to see hyper-reflective structures beneath the choroidal neovascular membranes, not accessible using the 830nm OCT.…”
Section: Discussionmentioning
confidence: 99%
“…The prototype swept-source OCT system was built by the Computational Optic Group at the University of Tsukuba. A detailed description of this system has been published [7,8,14]. The center wavelength of the probe beam was 1,060 nm.…”
Section: Subjectsmentioning
confidence: 99%
“…Enhanced depth imaging with commercial optical coherence tomography (OCT) at 840 nm provides two-dimensional line tomography and thickness of the choroid [5,6]. OCT using a 1-μm probe wavelength, the so-called high-penetration OCT, enables choroidal thickness measurement at arbitrary points in the macula [7][8][9]. These studies used point-bypoint measurements to provide important information regarding choroidal thickness [4-6, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Like their study, ours also found improved visualization of choroid with longer wavelength, however our study did not address presence or absence of specific pathologic features associated with the RPE and choroid. Similarly, Yasuno et al 13 found improved contrast of morphologies beneath the retinal pigment epithelium with their prototype ss-OCT (1060 nm; 28,000 depth scans/sec) compared with standard OCT without EDI. No comment was made regarding visibility of the vitreoretinal interface.…”
Section: Discussionmentioning
confidence: 87%
“…As far as we are aware, this has not been described in current studies evaluating longer wavelength ss-OCT. [8][9][10][11][12][13] Figure 1 demonstrates a case of neovascular AMD with vitreomacular adhesion not evident with the longer wavelength images. While no firm conclusions can be made regarding the clinical relevance of this specific finding, this case illustrates the potential loss of sensitivity to pathology at the retinal surface with use of these OCT modalities.…”
Section: Discussionmentioning
confidence: 99%